2018
DOI: 10.1111/pere.12234
|View full text |Cite
|
Sign up to set email alerts
|

Pornography use and marital quality: Testing the moral incongruence hypothesis

Abstract: Studies often report a negative association between pornography use and marital quality. A number of studies, however, find this negative association to be stronger among religious Americans, suggesting that “moral incongruence” may be a key moderating factor. This theory is tested with panel data from the nationally representative 2006–2012 Portraits of American Life Study (N = 612). Support for the theory is mixed. Any pornography use in 2006 predicts lower marital quality in 2012 regardless of whether the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…For example, Wright, Sun, et al's (2017) recent path analysis underscores the role that perceiving pornography to be a valid source of sexual information plays in the relationship between pornography use and sexual dissatisfaction, and research conducted by Blais-Lecours et al (2016) highlights the importance of pornography use-related distress to sexual satisfaction. Work by Perry (2018) suggests that one's opinion on the morality of pornography may moderate the relationship between pornography use and relationship quality, and as mentioned above, it is possible that the degree to which one's sexual partner is accommodating of one's sexual preferences may act to moderate the indirect effect of pornography use on sexual satisfaction through preference for porn-like sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wright, Sun, et al's (2017) recent path analysis underscores the role that perceiving pornography to be a valid source of sexual information plays in the relationship between pornography use and sexual dissatisfaction, and research conducted by Blais-Lecours et al (2016) highlights the importance of pornography use-related distress to sexual satisfaction. Work by Perry (2018) suggests that one's opinion on the morality of pornography may moderate the relationship between pornography use and relationship quality, and as mentioned above, it is possible that the degree to which one's sexual partner is accommodating of one's sexual preferences may act to moderate the indirect effect of pornography use on sexual satisfaction through preference for porn-like sex.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not detect a relationship between husbands' pornography use and sexual satisfaction in either direction. More recently, a large, nationally representative sample of married U.S. adults found that men's pornography use was predictive of self-reported marriage quality at a 6-year follow up (Perry, 2016(Perry, , 2018. In addition, there is some experimental evidence to indicate that pornography exposure negatively impacts satisfaction with one's sexual partner's physical appearance, sexual curiosity, and sexual performance (Zillmann & Bryant, 1988).…”
mentioning
confidence: 99%
“…Individuals who hold traditional religious beliefs likely have unique and potentially strong oppositional views on pornography. Along these lines, moral opposition to pornography strengthens the negative association between marital quality and consumption (Perry, 2018). Negative associations between pornography use and sexual satisfaction are similarly exacerbated for men with ties to conventional religion (Perry & Whitehead, 2019).…”
Section: Personal Views and Attitudesmentioning
confidence: 96%
“…That is, rather than inferring moral incongruence (i.e., moral disapproval among users), we defined incongruence as the interaction of use and disapproval, because this interaction is more consistent with previous definitions of moral incongruence (Grubbs et al, 2019a). Although past works have defined moral incongruence this way (interaction of disapproval and use), none have examined how such incongruence predicts self-reported dysregulation or self-reports of addiction (Perry, 2018a(Perry, , 2018b(Perry, , 2018c. Therefore, this is the first work to examine how the interaction of moral disapproval of pornography and the use of pornography is associated with self-reported problems with or addiction to pornography.…”
Section: The Present Studymentioning
confidence: 99%